Correlations between Self-care Behaviors and Anxiety, Family Support, and Disease State in Patients with Heart Failure and Type II Diabetes Mellitus Admitted to Chamran Teaching Health Center in Isfahan, Iran (2018) - T Najafi Ghezeljeh; A Ghasemi; M Rasouli; M Garak Yaraghi (Iran University of Medical Sciences, 2019)
Background & Aims: Heart failure is a prevalent, chronic disease in developing country, and type II diabetes mellitus is considered to be a major cause of heart failure. An effective approach to the control of these diseases is the active participation of patients in self-care. However, the concurrence of heart failure and diabetes is associated with complex and difficult self-care behaviors. Therefore, it is essential to identify the influential factors in self-care behaviors. The present study aimed to assess the correlations between self-care behaviors and anxiety, family support, and disease state in patients with heart failure and type II diabetes.  Materials & Methods: This descriptive-correlational study was conducted on 158 patients with heart failure and type II diabetes mellitus referring to Chamran Hospital in Isfahan, Iran in 2018. The patients were selected via continuous sampling. Data were collected using the European heart failure self-care behavior scale, Charlson comorbidity index, mini-mental state examination social support (family scale), Spielberger state-trait anxiety inventory, and a demographic questionnaire. Data analysis was performed in SPSS version 16 using descriptive statistics (frequency, frequency percentage, mean, and standard deviation) and inferential statistics (t-test and analysis of variance). Results: The majority of the patients (88.6%) had moderate self-care behaviors, with the mean score estimated at 38.37 ± 4.76. No significant correlations were observed between the demographic characteristics of the patients, their disease state, family support, and anxiety with self-care behaviors (P>0.05). Conclusion: According to the results, investigations must continue on the influential factors in self-care behavior in order to change the attitudes of patients in this regard, so that heart failure and type II diabetes could be controlled and their complications could be prevented.